Kill or cure? Different types of social class identification amplify and buffer the relation between social class and mental health. Issue 2 (4th March 2018) - Rubin, Mark; Stuart, Rebecca
ABSTRACT: The present research investigated different types of social class identification as moderators of the negative relation between social class and mental health problems. Psychology undergraduates ( N  = 355) completed an online survey that included measures of social class, mental health and well-being, and three aspects of social class identification: importance of identity, salience of identity, and perceived self-class similarity. Perceived self-class similarity buffered the negative association between social class and depressive symptoms. However, importance and salience of social class identity amplified the associations between social class and anxiety and life satisfaction. These findings contribute to a more sophisticated understanding of the way in which social identification may operate as a social cure.